2015
DOI: 10.12816/0024089
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of the Islamic Stock Market in a Prolonged Downturn in the Global Market : Empirical Evidence from Malaysia

Abstract: By focusing on Malaysian data, this study investigates the response of the Islamic stock market to changes in major macroeconomic variables such as industrial output, money supply, unemployment rate, exchange rate and foreign interest rate. It focuses on the period from January 2010 to December 2014 to capture the period of a prolonged downturn in the global financial market due to the U.S. financial crisis which started in 2007. The study adopts the cointegration approach of the Auto Regressive Distributed La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 27 publications
(31 reference statements)
3
12
0
Order By: Relevance
“…For example, (Chkili & Nguyen, 2014) found that exchange rate movements had no significant effect toward stock markets returns within BRICS countries (Brazil, Russia, India, China plus South Africa). However, (Mustafa et al, 2017) found a positive relationship between real exchange rate with Islamic Stock prices in Malaysia. While (Ayopo, Isola, & Olukayode, 2016) which Enquired the relation concerning GDP with stock prices found a positive relationship between GDP and conventional stock prices in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, (Chkili & Nguyen, 2014) found that exchange rate movements had no significant effect toward stock markets returns within BRICS countries (Brazil, Russia, India, China plus South Africa). However, (Mustafa et al, 2017) found a positive relationship between real exchange rate with Islamic Stock prices in Malaysia. While (Ayopo, Isola, & Olukayode, 2016) which Enquired the relation concerning GDP with stock prices found a positive relationship between GDP and conventional stock prices in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 90%
“…(Abugri, 2008) analyzed the effect of foreign interest rate on conventional stock prices in Latin America. While there were studies which investigated the relationship between foreign interest rate (using the Federal Fund Rate as proxy) in Islamic stock market index in Malaysia ( (Majid & Yusof, 2009) and (Mustafa, Ramlee, & Kassim, 2017)). Yet, these studies did not analyze whether domestic interest rate or foreign interest is more important in determining Islamic stock prices.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, due to the lack of data availability, there is still a lack of empirical studies on the link between the Islamic stock market or Islamic capital market in general and economic growth. Additionally, the studies in this area have mostly been theoretical (Mustafa et al, 2017). For instance, Ahmad and Alawode (2017) has notionally explained that Sukuk is important for economic development in terms of fiscal support, liquidity management, education, health, infrastructure, as well as the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, Autoregressive Distributed Lag (ARDL) model is more flexible in assessing the I(0) or I(1) conditions (Pesaran, Shin, & Smith, 2001). This explains why it was widely used in previous studies (Alhassan & Fiador, 2014;Bhattacharya, Bhattacharya, & Basu, 2019;Mustafa, Ramlee, & Kassim, 2016). ARDL is illustrated as follows (Pesaran, 2015):…”
Section: Operational Definition Of Variablesmentioning
confidence: 99%